The anatomy of post-communist regimes : a conceptual framework - Magyar, Bálint, 1952-; Madlovics, Bálint, 1993- (Central European University Press, 2020)
"This book offers a single, coherent framework of the political, economic, and social phenomena that characterize post-communist regimes. Focusing on Central Europe, the post-Soviet countries and China, the study provides concepts and theories to analyze the actors, institutions, and dynamics of post-communist democracies, autocracies, and dictatorships. The work explores the structural foundations of post-communist regime development; the types of state, with an emphasis on informality and patronalism; the types of actors in the political, economic, and communal spheres; the ways autocrats neutralize the institutions of public deliberation (media, elections, etc.); the color revolutions of civil resistance (as in Georgia and in Ukraine) and the defensive mechanisms of democracy and autocracy; the evolution of corruption and the workings of "relational economy"; an analysis of China as "market-exploiting dictatorship"; the sociology of "clientage society"; the instrumental use of ideology, with an emphasis on populism; and a six-regime framework for modeling regime trajectories. Written in textbook style, the book is suitable for both beginners who wish to understand the logic of post-communism and scholars who are interested in original contributions to comparative regime theory. The book is equipped with QR codes that link to a website, which contains interactive, 3D supplementary material for teaching"--